THE ROLE OF THE PROFITABILITY INDEX OF THE CRITERION CAMELS IN ACHIEVING BANKING GOVERNANCE REQUIREMENTS: A STUDY OF THE IRAQI BANK OF BAGHDAD (World Economics and Finance Bulletin, 2023)
To introduce the profitability index and the standard ratio determined by the Central Bank of Iraq based on and in line with the standard CAMELS, the role of this indicator and the extent of its contribution to the bank's growth and capital increase, as well as evaluating the performance of banks with the profitability index and indicating its impact on achieving the requirements of banking governance.
Keywords: standard CAMELS; profitability; banking governance; banking risks